Beyond discards: cascading socio-economic and environmental effects of a commercial aggregate landings program in Rhode Island - Livermore, Julia (Frontiers in Marine Science, 2023)
Flexible approaches to commercial fisheries harvest have been designed to meet management objectives. Rights-based management tools have been problematic for fishing businesses in certain scenarios, whereas aggregate landings approaches may offer similar flexibility while avoiding pitfalls like industry consolidation. This study evaluates a Rhode Island pilot aggregate landings program for summer flounder (Paralichthys dentatus) and black sea bass (Centropristis striata) from the perspective of the pilot program participants. Semi-structured interviews were conducted with participating commercial harvesters. Fishery-dependent data were also analyzed to supplement harvesters’ responses. Interview respondents overwhelmingly supported the aggregate landings approach and described benefits directly from the program, including cost savings, reduced discards, and improved safety. The program also led to increased average weekly harvest of both species and a slight increase in the price of catch for black sea bass for program participants. The aggregate landings approach encouraged fishers to take on less risk through added flexibility in when they chose to fish, while still maximizing their utility. Although the original goals of the program were to reduce regulatory discards and make businesses more efficient, it also resulted in improvements to fishers’ well-being, suggesting that aggregate landings approaches should be considered for other fisheries.